2015
DOI: 10.4250/jcu.2015.23.2.78
|View full text |Cite
|
Sign up to set email alerts
|

Left Ventricular Strain as Predictor of Chronic Aortic Regurgitation

Abstract: BackgroundIt is not well known about the implication of left ventricular (LV) strain as a predictor for mortality in patients with chronic aortic regurgitation (AR). The purpose of this study was to investigate whether global longitudinal strain measured by two-dimensional speckle-tracking echocardiography could predict long-term outcome in patients with chronic AR.MethodsThis is a single center non-randomized retrospective observational study. The patients with chronic AR from January 2002 to December 2012 we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(34 citation statements)
references
References 13 publications
0
30
0
2
Order By: Relevance
“…Moreover, impaired longitudinal and circumferential strain rates 6 months after MV repair have been associated with myofibrillar degeneration at the time of surgery, signifying the clinical value of impaired strain as an imaging biomarker of early myocardial dysfunction. Also for AR, long‐term studies show that GLS is an independent predictor of mortality or indications for surgery . Outcome studies with similar results have been conducted in AS patients …”
Section: Tissue Characterization and Myocardial Function Assessment Bmentioning
confidence: 75%
“…Moreover, impaired longitudinal and circumferential strain rates 6 months after MV repair have been associated with myofibrillar degeneration at the time of surgery, signifying the clinical value of impaired strain as an imaging biomarker of early myocardial dysfunction. Also for AR, long‐term studies show that GLS is an independent predictor of mortality or indications for surgery . Outcome studies with similar results have been conducted in AS patients …”
Section: Tissue Characterization and Myocardial Function Assessment Bmentioning
confidence: 75%
“…Upon reading the full texts, six papers were retained for analysis. All of the studies were observational and published between 2011 and 2018 ( 9 , 10 , 11 , 12 , 13 , 14 ). In this report, we first describe studies’ characteristics, and then we elaborate on the outcomes.…”
Section: Resultsmentioning
confidence: 99%
“…Of interest, Park et al 17 reported a significant discordance between the presence of CR and the LV dimension recommended for aortic valve replacement. In their study, one‐third of patients with larger dimensions had significant CR, whereas one‐third of patients with smaller LV dimensions not qualifying for surgery did not have CR, suggesting that exercise test may be able to further stratify the risk for aortic valve replacement.…”
Section: Discussionmentioning
confidence: 99%